IMPACT OF BRAND IMAGE, PHYSICAL EVIDENCE, DIGITAL PROMOTION, AND PRODUCT QUALITY ON SALES OF MS GLOW PRODUCTS IN SIDOARJO - Sanggarwati, Diah Ayu; Hermawati, Elok; Kuswandi, Kuswandi (Jurnal Manajemen, 2023)
This study examines the effect of brand image, physical evidence, digital promotion, and product quality on sales of MS Glow products in Sidoarjo. This study uses a quantitative method with a descriptive approach. The sample in this study were 55 members of the Dennis Love Shop. This sample was taken using a saturated sampling technique. Data processing using statistical software SPSS 25. The results of the study are as follows, brand image, physical evidence, digital promotion and product quality have a significant effect both partially and simultaneously on sales and in this study product quality has the most significant effect on sales.